PEMBELAJARAN LINGKARAN DENGAN PENDEKATAN PEMECAHAN MASALAH VERSI POLYA PADA KELAS VIII DI SMP PGRI 01 DAU - Priyo Utomo, Dwi (Widya Warta, 2012)
The purposes of this study are to (1) understand the patterns of students’ mathematic problem solving with the version of the Polya problem-solving approach and (2) find out the difficulties faced by students in solving mathematic problem.This research is descriptive qualitative in nature. The object of this research is the eighth year students of junior high school PGRI 01 Dau on a circle of material. Data collecting was done using test sheet that aims to determine the patterns of students' mathematic problem solving, so that the results of the test can also show the difficulties encountered by the students. The data analysis showed that (1) the students were able to perform stage version of the Polya problem solving on measures of understanding about and plan for the settlement, but there were 16 students who were able to plan the implementation phase and half of the students (10) were able to do the checking stage again and (2) as many as 0% of thestudents found difficulty in understanding problem and planning stages of completion, meaning no student had difficulty in understanding the problem and plan for completion.But there were 17% of the total number of the students who got difficulty in implementing the plan, and there were 47% of the total number of the students who encountered difficulty at this stage of review.